Determinants of adopting sustainable agricultural livelihoods among ethnic minority households in a Luoi 4, Hue City, Vietnam - Hang, Huynh Thi Diem; Long, Nguyen Kim; Huong, Nguyen Thi Minh; Hanh, Le Ngoc; Son, Nguyen Hoang (Asian Journal of Agriculture and Rural Development, 2026)
This study aims to identify the determinants influencing households’ adoption of sustainable agricultural livelihood models in A Luoi 4 commune, Hue City, Vietnam. Based on a household survey of 212 respondents and using a binary logistic regression model, the research examines the effects of 28 independent variables representing human, natural, physical, financial, and social capitals. The model identifies nine significant factors shaping the likelihood of adopting sustainable livelihood practices: ethnicity, access to local financial support, access to output markets, stability of current livelihood, participation in farmer groups or cooperatives, exposure to climate change impacts, perception of climate change, access to agricultural information, and educational attainment. These results highlight that a single factor does not drive livelihood adoption but emerges from the interaction of socio-economic conditions, institutional connections, and environmental stressors. Households with stronger cognitive awareness, better market and institutional access, or higher disaster exposure are more likely to shift toward sustainable livelihood practices. The findings underscore the need for targeted interventions that enhance education, strengthen local cooperatives, improve financial support schemes, and expand market linkages for ethnic minority communities. By providing empirical evidence on livelihood decision-making in upland areas, the study contributes to the design of inclusive, climate-adaptive development policies that support resilient livelihood transitions in mountainous regions.